Peran Kepala Sekolah Dalam Pelaksanaan Manajemen Berbasis Sekolah di SMA Negeri 1 Kutacane - Nur Azizah; Siti Khalijah Simanjuntak; Neliwati Neliwati (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This article aims to determine the role of school principals in the implementation of school-based management. This study uses qualitative methods with a descriptive approach. The location of this research is SMA Negeri 1 Kutacane. Data collection techniques in writing this article are interviews and field observations. The purpose of this study is to identify and describe the professionalism of school principals in implementing school-based management. Based on the findings in the field, the role of the school principal in implementing school-based management is already professional. The school principal is a role model, a motivator for educators and education staff. The researcher concluded that the school principal had carried out his role in the field of leadership, motivating teachers, and improving educational infrastructure well in the implementation of school-based management. The researcher suggests that school principals should continue to improve their professionalism in carrying out their roles so that the existence of educational institutions is increasingly recognized and trusted by the community. Keywords: The Role of the Principal, School Based Management, Education